Reinforcement of polypropylene with alkali-treated sugarcane bagasse fibers: Mechanism and consequences. (10th November 2020) - Bartos, András; Utomo, Benny Putra; Kanyar, Barnabás; Anggono, Juliana; Soetaredjo, Felycia Edi; Móczó, János; Pukánszky, Béla
Abstract: Polypropylene composites were prepared from neat and alkali-treated sugarcane bagasse fibers. The results showed that alkali treatment leads to an increase in composite stiffness and strength. A maximum is achieved in these properties at around 5 wt% NaOH content of the treating solution. The increase in properties was assigned to the improvement in inherent fiber characteristics. Acoustic emission testing and electron microscopy showed that the two main local deformation processes related to the fibers are their fracture and debonding; the latter is accompanied by the shear yielding of the matrix. Increased inherent strength of the fibers results in an increase in the fracture initiation stress and fracture energy of the composites. Interfacial adhesion has a slight effect on stiffness, but more significant on strength and impact resistance. Changing adhesion modifies the relative importance of local deformation processes, the number of debonding events decreases, while fiber fracture increases with increasing adhesion. Increased interfacial adhesion improves stress transfer and the load bearing capacity of the fibers as well, but suppresses matrix yielding. Alkali treatment increases inherent fiber strength, which can be directly correlated with composite strength. Graphical abstract: Image 1